Postcolonial, decolonial research dilemmas: fieldwork in Australian Indigenous contexts. (October 2018) - Exley, Beryl; Whatman, Susan; Singh, Parlo
We come to this article as non-Indigenous teacher educators working as qualitative researchers in postcolonial/decolonial (Mignolo, 2000) times. We explore matters related to schooling in remote Australian Indigenous communities. In this article, we respond to Delamont's invitation for qualitative researchers to revisit (Delamont and Hamilton, 1984) and think reflexively (Delamont, 2009) about our field work research methods. In doing so, attention is drawn to research processes involved with observing, narrating and writing lives and experiences. We highlight matters related to sequencing dilemmas (Delamont, 2009), the need to locate the self-as-researcher in the social (Delamont, 2007), and calling out ethical tensions associated with the 'catch 22' of confidentiality and acknowledgement (Delamont, 2007). Two separate researcher recounts of field notes are used to render visible our reflexive thinking as we attempt to negotiate Western educational research ethics policies and procedures and ways of knowing and being in Indigenous contexts.